(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
In this article the existence of the arcs in the projective plane of order has been proved. For we have shown that the arcs are complete. The existence of the completes (144,12)-arc in , (256,16)-arc in and - (324,18)arc in have been found.